Business Strategy Analysis Using SWOT And QSPM: A Case Study of Naz Cake and Cookies Bandar Lampung - Duta, Trio Arya; Sari, Aida; Ambarwati, Dwi Asri Siti (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to evaluate the business strategy of Naz Cake & Cookies using the SWOT and QSPM methods. To address increasing competition, effective business strategies are necessary for the company to sustain and grow. The SWOT method is employed to identify the internal and external factors affecting the company. After identifying the SWOT factors, the QSPM method is applied to evaluate and select the most appropriate alternative strategies based on the identified factors. The analysis results suggest that the most effective strategy to implement is increasing production volume to maintain customer trust. Additionally, strategies such as offering discounts near closing time are also considered important to support the company's growth. Recommendations include increasing production, optimizing the use of digital marketing, and reorganizing product layout to enhance visual appeal and customer experience. With these strategies, Naz Cake & Cookies is expected to maintain and improve its competitiveness in the market.